America the beautiful : Tennessee - McNair, Sylvia (Chicago : Childrens Press, 1990)
Introduces the geography, history, government, economy, industry, culture, historic sites, and famous people of the Volunteer State.
Includes index.
6.9
5-8
Keywords: Tennessee -- Juvenile literature; Tennessee; Tennessee